Speech and Language Therapy in Slovenia: Education, Career Prospects and Treatment of Speech and Language Disabilities - Ivanuš Grmek, Milena; Mithans, Monika; Plavčak, Darja (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
Speech and language therapy is a discipline dedicated to identifying, treating and preventing speech and language disabilities, thereby making an important contribution to improving people's communication skills. This chapter examines the contributions of speech and language therapists in Slovenia, focusing on their educational pathways, career prospects and the various professional settings they engage with, including healthcare, education and social care environments. A significant emphasis is placed on the education of speech and language therapists, equipping students with the necessary competencies to assist individuals with speech and language disabilities. The chapter also addresses the increasing demand for qualified professionals and the importance of early and integrated treatment for individuals of all ages. The conclusion stresses the need to expand training opportunities and enhance access to speech and language therapy services in Slovenia.